Economic complexity and housing deficit: an econometric analysis in Brazil - Andreoli, Ana Cláudia [UNESP]; Ferraz, Diogo [UNESP]; Mariano, Enzo Barberio [UNESP] (FapUNIFESP (SciELO), 2023)
Paper aims: Housing is pivotal in advancing the quality of life. This study investigates the impact of economic complexity on the housing deficit within the Brazilian states. Originality: Several studies have investigated the significance of social policies and economic growth as explanatory factors for housing deficits. Our study sheds light on the importance of economic structure in facilitating improved housing conditions for individuals. Research method: The Fixed Effects Driscoll Kraay (FE-DK) econometric model was employed, utilizing panel data encompassing 27 Brazilian federative units spanning 2009 to 2017. Main findings: The primary finding of this research elucidates the role of economic complexity as a determining factor that significantly impacts the housing deficit within Brazilian states. In other words, an enhanced economic structure contributes to improved housing conditions for the population and fosters a higher quality of life. Implications for theory and practice: Theoretically, this paper posits the existence of a novel determinant that elucidates the housing and housing deficit theory. Moreover, the study makes a substantive contribution by advocating for public policies to facilitate housing conditions and enhance social well-being within a developing country. It underscores the pivotal significance of the productive structure in driving the economic development of the nation.
Keywords: Economic growth; Housing deficit; Production structure; Public policy